The legacy of Soviet dissent : dissidents, democratisation and radical nationalism in Russia - Horvath, Robert, 1966- (BASEES/RoutledgeCurzon series on Russian and East European studies, 2005)
This important book argues that the dissident movement between the mid-1960s and the mid-1980s had profound repercussions for Gorbachev's reforms and for the post-Soviet order.